To better and effective reading in EFL through context - Danelia, Ira (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
For decades different approaches or methods have been used to teach and improve all skills while teaching English. These approaches differ in how much guidance or direction teachers provide as their students are learning new skills, how clearly and directly teachers explain new skills, whether they demonstrate exactly how to use a specific skill, and whether the skills are taught in a thoughtful sequence. One of these skills is reading, a complex process, especially in a foreign language. Reading comprehension in both EFL and ESL (at university levels) is affected by many factors. One of the most important among them is vocabulary knowledge. It is worth mentioning that vocabulary knowledge is not something that can ever be fully mastered. It is a life-long process and recently the importance of vocabulary teaching-learning is increasing more and more. One of the most useful strategies for developing vocabulary knowledge is vocabulary learning through context. The purpose of the present article is to overview the different suggestions of the researchers about factors that affect vocabulary acquisition through context which leads to better reading. To find out how effectively and often the strategy in question is used in language groups at Sokhumi State University, the research team was composed of three full-time English teachers and six undergraduate students of English Philology. A qualitative (interview) approach was used to study how the learners are taught the strategies discussed in this article in an ordinary classroom. Each participant in the study was given open-ended questions.